2020
DOI: 10.3390/s20143958
|View full text |Cite
|
Sign up to set email alerts
|

Playability and Player Experience in Digital Games for Elderly: A Systematic Literature Review

Abstract: A higher number of people increasingly uses digital games. This growing interest in games, with different objectives, justifies the investigation of some aspects and concepts involved, such as product quality (game), usability, playability, and user or player experience, topics investigated by the multidisciplinary area called Human–Computer Interaction (HCI). Although the majority of users of these games are children and young people, an increasing number of older adults join technology and use different type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…7. Offering customizable fonts or icons can provide a more satisfying player experience for older adults, according to previous studies (Al Mahmud et al, 2012;Doroudian et al, 2020;Mubin et al, 2008) and a review by Rienzo and Cubillos (2020) in playability and player experience in digital games for older adults. Building on this finding, we started the first iteration with a prototype that incorporated a customization feature.…”
Section: Design Guidelinesmentioning
confidence: 98%
See 1 more Smart Citation
“…7. Offering customizable fonts or icons can provide a more satisfying player experience for older adults, according to previous studies (Al Mahmud et al, 2012;Doroudian et al, 2020;Mubin et al, 2008) and a review by Rienzo and Cubillos (2020) in playability and player experience in digital games for older adults. Building on this finding, we started the first iteration with a prototype that incorporated a customization feature.…”
Section: Design Guidelinesmentioning
confidence: 98%
“…The research literature has shown that playing digital games can contribute to improving older adults' well-being, but the research is still at an early stage (Rienzo & Cubillos, 2020). In addition, there is a clear knowledge gap where digital games that were designed pre-pandemic may not be suitable in meeting the special needs of older adults playing digital games due to the sheltering measures under the pandemic (e.g., digital games having only a singleplayer mode, digital games requiring other players to be physically together, digital games being difficult to understand without guidance and assistance given in person, etc.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…CSGs fall within the subset of serious gaming -gaming for purposes beyond entertainment. Research has been increasingly interested in the playability and player experiences of these games (Rienzo and Cubillos 2020). Although player experience was previously considered as simply player satisfaction, the player experience of serious games has now been understood, generally, as a combination of many factors including immersion, challenge, and emotion, among others (d 'Ornellas et al 2015;Rienzo and Cubillos 2020;Wiemeyer et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The link between user and player experience provides specific assessment tools in specific gaming environments, and there are several techniques that are recommended, particularly for games [ 41 ].…”
Section: Introductionmentioning
confidence: 99%